Optimization of Vinyl Acetate Synthesis Process - D. A. Asrorov, B. Sh. Omanov, N. I. Fayzullaev, N. Kh. Musulmonov, M. S. Xatamova (International Journal of Control and Automation, 2020)
In this paper, we consider the texture characteristics of the developed highly active catalyst (ZnO)x (CdO)y (ZrO₂)z for the catalytic acetylation of acetylene based on the Sol-Gel technology, and also study the effect of some parameters (temperature, volumetric rate, C₂H₂ molar ratio : CH₃COOH, catalyst preparation procedure) for the course of this process. Based on the results obtained, a kinetic model is created that satisfies the synthesis of vinyl acetate. Taking into account the catalyst deactivation, a mathematical model of the displacement reactor and determination of the main parameters of the tubular reactor was developed for the synthesis of vinyl acetate from acetylene and acetic acid. Using the developed nano-catalyst, the kinetic laws of vinyl acetate synthesis were studied, the material balance of the process was calculated, and an improved technological scheme for the synthesis of vinyl acetate was proposed. On the basis of stored information, vinyl acetate synthesis process has been optimized.